Thiophene-ethylenedioxythiophene hybrid monomer as well as preparation method and application thereof

Through the synthesis of thiophene-ethylenedioxythiophene hybrid monomers, D-A polymer is formed, which solves the problems of insufficient chemical stability and response speed of existing electrochromic materials, and achieves efficient electrochromic effect.

CN119119086APending Publication Date: 2024-12-13WUYI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411054008.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing electrochromic materials have shortcomings in terms of chemical stability, response speed and color variation range, especially the electrochromic effect of thiophene unit-based polymers is poor.

Method used

The thiophene-ethylenedioxythiophene hybrid monomer is synthesized through Stille/Suzuki palladium catalytic cross-coupling reaction to form D-A polymer, adjust the type and mass ratio of thiophene units, optimize the conjugation relationship, and form excellent electrochemical activity and Electrochromic materials with redox stability.

Benefits of technology

The electrochromic materials are achieved with good optical contrast, fast response time and high coloring efficiency, improving the electrochemical stability and color change efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119086A_ABST
    Figure CN119119086A_ABST
Patent Text Reader

Abstract

The invention discloses a thiophene-ethylenedioxythiophene hybrid monomer as well as a preparation method and application thereof, and belongs to the technical field of new materials. The thiophene-ethylenedioxythiophene hybrid monomer provided by the invention is thiophene, bithiophene or a prepolymer of the bithiophene and the ethylenedioxythiophene; the electrochromic material formed by polymerizing a monomer formed by hybridizing ethylenedioxythiophene has excellent electrochemical activity and oxidation-reduction stability, has good optical contrast in near and infrared regions, and is sensitive in response and high in coloring efficiency under visible light. The invention also provides a preparation method and application of the thiophene-ethylenedioxythiophene hybrid monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a thiophene-ethylenedioxythiophene hybrid monomer and a preparation method and application thereof. Background Art

[0002] Electrochromism refers to the reversible change of the optical properties of a specific material under the action of an external voltage, which is manifested in the reversible change of color and transparency in appearance. Electrochromic (EC) materials are a class of materials that can reversibly change their optical properties under electrical stimulation. They have great potential in applications such as smart windows, electronic paper and military camouflage.

[0003] The first generation of electrochromic viologens or certain gels have problems such as poor chemical stability, easy leakage, short life and high power consumption. The second generation of electrochromic materials uses inorganic non-metallic materials such as tungsten trioxide (WO 3 ), although the chemical stability and service life are further improved, the color change speed of this type of material is usually slow and the color change range is limited. The third generation of electrochromic materials uses conductive polymer-based electrochromic materials, which have attracted widespread attention due to their good processability, diverse color selection, high contrast and fast response time; researchers have been exploring and developing excellent electrochromic materials in the field of organic polymers in the new third generation.

[0004] Polymers based on different thiophene units (such as thiophene, bithiophene, bithiophene, etc.) have been synthesized and applied to construct optoelectronic devices. Among them, the bithiophene unit (BT) has attracted the attention of researchers due to its ease of construction and excellent device performance. The bithiophene unit plays multiple roles in the field of organic semiconductors: as an excellent monomer for the synthesis of conjugated copolymer systems, because the optoelectronic materials constructed by it have good carrier mobility; and as a suitable donor unit in DA polymers (donor-acceptor polymers) to reduce the energy band gap. These properties indicate that the bithiophene unit is an ideal choice for constructing functional copolymers. Encouraged by these results, many bithiophene-based polymers have been developed and used to construct organic electronic devices. For example, poly (dioctylthiophene-alt-bithiophene) (also known as F8T2) is one of the widely studied materials, which shows very high performance when used to construct OFETs (organic field effect transistor) devices.

[0005] Currently, terthiophenes are important building blocks in the field of organic electronics. They are widely used in organic solar cells, organic field effect transistors (OFETs), organic light-emitting diodes (OLEDs), and organic photodetectors. Terthiophenes (such as 5,5”-dihexyl-2,2':5',2”-terthiophene) are often used to construct high-performance organic semiconductors due to their good solubility and self-assembly ability. Studies have shown that terthiophene compounds have excellent charge transport properties, which makes them very useful in the preparation of n-type and p-type semiconductors.

[0006] However, pure thiophene unit-based polymers do not have significant electrochromic effects, or the effects are relatively poor. Summary of the invention

[0007] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a thiophene-ethylenedioxythiophene hybrid monomer, and an electrochromic polymer (a DA polymer) formed by polymerization thereof has excellent electrochemical activity and redox stability, and has good optical contrast in the near and infrared regions, sensitive response under visible light, and high coloring efficiency.

[0008] The present invention also provides a method for preparing the thiophene-ethylenedioxythiophene hybrid monomer.

[0009] The present invention also provides application of the thiophene-ethylenedioxythiophene hybrid monomer.

[0010] According to an embodiment of the first aspect of the present invention, a thiophene-ethylenedioxythiophene hybrid monomer is provided, wherein the thiophene-ethylenedioxythiophene hybrid monomer is at least one of the compounds represented by formula I to formula III:

[0011]

[0012] The thiophene-ethylenedioxythiophene hybrid monomer according to the embodiment of the present invention has at least the following beneficial effects:

[0013] The thiophene-ethylenedioxythiophene hybrid monomer includes a thiophene unit (monothiophene, dithiophene or terthiophene) and an ethylenedioxythiophene (EDOT) unit, which form a conjugated relationship. The polymer synthesized therefrom has significant electrochromic properties. On the basis of the above conjugated relationship, the type of thiophene unit used (i.e., the mass specific gravity of the thiophene unit and the conjugated length) is further adjusted to adjust the optical contrast, electrochemical stability and coloring efficiency of the obtained electrochromic material.

[0014] Furthermore, in the thiophene-ethylenedioxythiophene hybrid monomer provided by the present invention, both ends are capped (hybridized) with ethylenedioxythiophene. Compared with the monomer capped on one side with thiophene-ethylenedioxythiophene, in the thiophene-ethylenedioxythiophene hybrid monomer provided by the present invention, the thiophene unit and the EDOT unit atomic orbitals are recombined to form a new hybrid orbital, forming a more stable and stronger chemical bond, having a better conjugated relationship, and the performance of the electrochromic material obtained by polymerization thereof is better.

[0015] On the whole, the present invention optimizes the electrochromic performance by means of thiophene-EDOT hybridization, so that the provided thiophene-ethylenedioxythiophene hybrid monomer (or the polymer formed thereof) has good electrochemical stability, coloring efficiency, short response time and high optical contrast.

[0016] According to some embodiments of the present invention, the initial oxidation potential of the compound represented by Formula I (abbreviated as EDOT-T) is 0.55V.

[0017] According to some embodiments of the present invention, the initial oxidation potential of the compound represented by Formula II (abbreviated as EDOT-2T) is 0.55V.

[0018] According to some embodiments of the present invention, the initial oxidation potential of the compound represented by Formula III (abbreviated as EDOT-3T) is 0.6V.

[0019] Since the thiophene-ethylenedioxythiophene hybrid monomer has a lower initial oxidation potential, it is easier to form a high-quality electrochromic material layer (thin film) in the subsequent electrochemical polymerization process.

[0020] According to some embodiments of the present invention, the thiophene-ethylenedioxythiophene hybrid monomer appears as a yellow to orange solid.

[0021] According to an embodiment of the second aspect of the present invention, there is provided a method for preparing the thiophene-ethylenedioxythiophene hybrid monomer, the method comprising the following steps:

[0022] A Stille / Suzuki palladium-catalyzed cross-coupling reaction was performed between the halogenated thiophene monomer and 5-tributyltin-3,4-vinyldioxythiophene;

[0023] The structural formula of the halogenated thiophene monomer is shown in any one of Formula IV to Formula VI:

[0024]

[0025] Wherein, R is a halogen atom.

[0026] When R is selected from a bromine atom, the mechanism of the preparation method is as follows:

[0027]

[0028] Since the preparation method adopts all the technical solutions of the thiophene-ethylenedioxythiophene hybrid monomer of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0029] Furthermore, in the preparation method of the present invention, the point-specific connection between the thiophene monomer and EDOT is achieved by selecting the preparation raw materials, and the thiophene-ethylenedioxythiophene hybrid monomer with the structure shown in Formula I to Formula III can be formed. That is, the preparation method is simpler and more accurate.

[0030] According to some embodiments of the present invention, in the halogenated thiophene monomer, R is selected from a chlorine atom or a bromine atom.

[0031] According to some embodiments of the present invention, the method for preparing 5-tributyltin-3,4-ethylenedioxythiophene comprises the following steps:

[0032] A1. Mix EDOT and n-BuLi at low temperature and stir;

[0033] A2. The mixture obtained in step A1 is mixed with tributyltin chloride and reacted;

[0034] A3. Remove impurities.

[0035] Thus, a tination reaction can occur at the α position of EDOT to obtain the 5-tributyltin-3,4-vinyldioxythiophene.

[0036] According to some embodiments of the present invention, in step A1, the low temperature has a temperature range of -70 to -80°C, for example, about -75°C or about -78°C.

[0037] According to some embodiments of the present invention, in step A1, the mass molar ratio of EDOT to n-BuLi is 1 g:5-10 mmol, for example, about 1 g:7 mmol, 1 g:8 mmol or about 1 g:9 mmol.

[0038] According to some embodiments of the present invention, in step A1, the mixing method includes:

[0039] providing a THF solution of EDOT; providing a hexane solution of n-BuLi;

[0040] At the low temperature, the hexane solution is added dropwise to the THF solution.

[0041] In the THF solution, the mass volume ratio of the solute to the solvent is 1 g:18-22 mL, for example, about 1 g:20 mL.

[0042] The concentration of the hexane solution is 2 to 3 mol / L, for example, about 2.5 mol / L.

[0043] The dropwise addition time is 25 to 35 minutes, for example, about 30 minutes.

[0044] According to some embodiments of the present invention, in step A1, the stirring time is 2.5 to 3.5 hours, for example, about 3 hours.

[0045] In step A1, the mixing and stirring are both performed at the low temperature.

[0046] According to some embodiments of the present invention, step A1 is performed in a protective atmosphere.

[0047] According to some embodiments of the present invention, in step A2, the volume mass ratio of the tributyltin chloride to the EDOT in step A1 is 2-3 mL:1 g, for example, about 2.5 mL:1 g.

[0048] According to some embodiments of the present invention, in step A2, the mixing temperature is the low temperature.

[0049] According to some embodiments of the present invention, in step A2, the reaction temperature is 20-30° C., for example, about 25° C., which is usually referred to as room temperature.

[0050] According to some embodiments of the present invention, in step A2, the reaction time is 8 to 15 hours, for example, about 9 hours, 10 hours, 12 hours or about 13 hours.

[0051] According to some embodiments of the present invention, in step A3, the impurity removal includes water washing and rotary evaporation performed in sequence, wherein the water washing can remove the solvent THF and unused reactants; and the rotary evaporation can remove water and unremoved solvent.

[0052] According to some embodiments of the present invention, the molar ratio of the halogenated thiophene monomer to the 5-tributyltin-3,4-ethylenedioxythiophene is 1:2-2.5, for example, about 1:2.2 or about 1:2.3.

[0053] According to some embodiments of the present invention, the Stille / Suzuki palladium-catalyzed cross-coupling reaction is carried out with the assistance of a palladium catalyst.

[0054] The palladium catalyst includes a catalyst [tetrakis(triphenylphosphine)palladium].

[0055] The molar ratio of the catalyst to the halogenated thiophene monomer is 1:20 to 30, for example, about 1:23, 1:25 or about 1:28.

[0056] According to some embodiments of the present invention, the Stille / Suzuki palladium-catalyzed cross-coupling reaction is carried out in a solvent.

[0057] The solvent used includes at least one of toluene and dimethylformamide.

[0058] The solvent is a mixture of toluene and dimethylformamide in a volume ratio of 3.5 to 4.5:1. For example, the specific volume ratio may be about 4:1.

[0059] The molar volume ratio of the halogenated thiophene monomer to the solvent is 8 to 25 mmol / L, for example, about 9 mmol / L, 10 mmol / L, 15 mmol / L, 20 mmol / L, 21 mmol / L, 22 mmol / L or about 23 mmol / L.

[0060] According to some embodiments of the present invention, the Stille / Suzuki palladium-catalyzed cross-coupling reaction is carried out in a protective atmosphere.

[0061] According to some embodiments of the present invention, the temperature of the Stille / Suzuki palladium-catalyzed cross-coupling reaction is 110-130° C., for example, specifically about 120° C.

[0062] According to some embodiments of the present invention, the Stille / Suzuki palladium-catalyzed cross-coupling reaction lasts for 24 to 48 hours, for example, about 36 hours.

[0063] According to some embodiments of the present invention, the method for preparing the thiophene-ethylenedioxythiophene hybrid monomer further comprises purifying the product after the Stille / Suzuki palladium-catalyzed cross-coupling reaction.

[0064] Purification of the product includes sequentially washing the organic phase, distillation under reduced pressure and silica gel column chromatography.

[0065] Purifying the product also includes filtering the mixture obtained by the Stille / Suzuki palladium-catalyzed cross-coupling reaction with diatomaceous earth before the extraction, thereby further improving the efficiency of subsequent washing of the organic phase.

[0066] The method for washing the organic phase is water washing.

[0067] The reduced pressure distillation is directed to the organic phase after water washing.

[0068] The eluent used in the silica gel column chromatography is a mixture of dichloromethane and petroleum ether in a volume ratio of 1:2.5 to 3.5. The specific volume ratio can be about 1:3. Furthermore, the solution produced by elution needs to be further desolventized to obtain a solid thiophene-ethylenedioxythiophene hybrid monomer.

[0069] According to some embodiments of the present invention, the method for preparing the thiophene-ethylenedioxythiophene hybrid monomer has a yield of the target product of ≥10%, for example, about 15%, 17%, 20%, 25%, 28% or about 30%.

[0070] According to an embodiment of the third aspect of the present invention, an electrochromic material is provided. The electrochromic material is a polymerization product of the thiophene-ethylenedioxythiophene hybrid monomer.

[0071] Since the electrochromic material adopts all the technical solutions of the thiophene-ethylenedioxythiophene hybrid monomer of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0072] That is, the electrochromic material has excellent electrochemical activity and redox stability.

[0073] According to some embodiments of the present invention, after 1000 cycles, the electrical activity retention rate of P(EDOT-3T) (polymerization product of EDOT-3T) is ≥ 83%, for example, about 83.5% or about 84%.

[0074] According to some embodiments of the present invention, the optical band gap of P(EDOT-3T) is 1.72 eV.

[0075] According to some embodiments of the present invention, after 100 cycles, the electrical activity retention rate of P(EDOT-2T) (polymerization product of EDOT-2T) is ≥ 93%, for example, about 93.5%, 94% or about 95%.

[0076] According to some embodiments of the present invention, after 500 cycles, the electrical activity retention rate of P(EDOT-2T) is ≥ 75%, for example, about 76%, 77%, 78%, 79% or about 80%.

[0077] According to some embodiments of the present invention, after 1000 cycles, the electrical activity retention rate of P(EDOT-2T) is ≥ 60%, for example, about 61%, 62%, 63%, 64% or about 65%.

[0078] According to some embodiments of the present invention, the optical band gap of P(EDOT-3T) is 1.75 eV.

[0079] According to some embodiments of the present invention, after 1000 cycles, the electrical activity retention rate of P(EDOT-T) (polymerization product of EDOT-T) is ≥ 95%, for example, about 96%, 97% or about 98%.

[0080] Since the electrochromic material has excellent electrochemical activity and redox stability, the electrochromic material is expected to be widely used in the preparation of electrochromic devices.

[0081] According to some embodiments of the present invention, the optical contrast ratio of P(EDOT-2T) in the near-infrared region is ≥ 44%, for example, about 45%.

[0082] According to some embodiments of the present invention, the optical contrast ratio of P(EDOT-3T) in the near-infrared region is ≥ 44%, for example, specifically about 45%.

[0083] According to some embodiments of the present invention, the response time of P(EDOT-T) under visible light is ≤ 0.8 s, for example, it may be about 0.6 s or about 0.5 s.

[0084] According to some embodiments of the present invention, the coloring efficiency of P(EDOT-T) at 490 nm is ≥159 cm 2 / C. For example, it can be about 160cm 2 / C.

[0085] According to some embodiments of the present invention, the coloring efficiency of P(EDOT-T) at 755 nm is ≥160 cm 2 / C. For example, it can be about 161cm 2 / C, 162cm 2 / C, 163cm 2 / C or about 165cm 2 / C.

[0086] The fast response time and high coloring efficiency further contribute to the wide application of the electrochromic material in the preparation of electrochromic devices.

[0087] According to an embodiment of the fourth aspect of the present invention, there is provided a method for synthesizing the electrochromic material, the method comprising electrochemically polymerizing the thiophene-ethylenedioxythiophene hybrid monomer.

[0088] Since the synthesis method adopts all the technical solutions of the electrochromic material of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0089] In traditional technology, chemically initiated polymerization is mostly used, which requires the addition of additional initiators, which not only increases material costs but also makes subsequent impurity removal difficult; the present invention adopts an electrochemical polymerization method, which has the effect of saving costs and simplifying the process.

[0090] According to some embodiments of the present invention, the electrochemical polymerization is carried out in a three-electrode system; wherein,

[0091] The material of the counter electrode used was platinum;

[0092] The reference electrode used was an Ag / AgCl electrode;

[0093] The working electrode used is a platinum electrode or an ITO electrode; during the electrochemical polymerization process, the electrochromic material is deposited on the surface of the working electrode; compared with coating after chemical initiation of polymerization, the thickness and texture of the electrochromic material deposited on the surface of the working electrode are more uniform.

[0094] The electrolyte used includes the thiophene-ethylenedioxythiophene hybrid monomer. The concentration of the thiophene-ethylenedioxythiophene hybrid monomer in the electrolyte is 0.008-0.012 mol / L, for example, specifically about 0.01 mol / L.

[0095] According to some embodiments of the present invention, the electrolyte further comprises Bu 4 NPF 6 of dichloromethane solution. 4 NPF 6 The concentration of the electrolyte is 0.08-0.12 mol / L, for example, specifically about 0.1 mol / L.

[0096] According to some embodiments of the present invention, the electrochemical polymerization is performed in a protective atmosphere.

[0097] According to some embodiments of the present invention, the electrochemical polymerization method comprises constant potential electrochemical polymerization.

[0098] According to some embodiments of the present invention, the potential used in the constant potential electrochemical polymerization is 0.6-0.9 V. For example, it may be about 0.7 V or about 0.8 V.

[0099] According to some embodiments of the present invention, the duration of the constant potential electrochemical polymerization is 20 to 50 seconds, for example, specifically about 40 seconds.

[0100] According to an embodiment of a fifth aspect of the present invention, there is provided an electrochromic glass, the electrochromic glass comprising an ITO substrate layer and an electrochromic material attached to a surface of the ITO substrate layer.

[0101] Since the electrochromic glass adopts all the technical solutions of the electrochromic material of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0102] According to an embodiment of the sixth aspect of the present invention, a method for manufacturing the electrochromic glass is provided, and the manufacturing method comprises the following steps: in a three-electrode system, ITO glass is used as a working electrode, a liquid phase containing the thiophene-ethylenedioxythiophene hybrid monomer is used as an electrolyte, and the electrochromic material is electrochemically deposited on the working electrode at a constant voltage.

[0103] Since the manufacturing method adopts all the technical solutions of the electrochromic glass of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0104] According to some embodiments of the present invention, the voltage of the constant voltage electrochemical deposition is 0.6-0.9 V. For example, it may be about 0.7 V or about 0.8 V.

[0105] According to some embodiments of the present invention, the duration of the constant voltage electrochemical deposition is 20 to 50 seconds, for example, specifically about 40 seconds.

[0106] In the preparation method of the sixth aspect of the present invention, other parameters are similar to those of the synthesis method of the fourth aspect of the present invention, except that in the preparation method, only ITO glass can be used as the working electrode.

[0107] According to an embodiment of the seventh aspect of the present invention, an electrochromic product is provided, wherein the raw materials for preparing the electrochromic product include the thiophene-ethylenedioxythiophene hybrid monomer, or the electrochromic material, or the electrochromic glass.

[0108] Since the electrochromic product adopts all the technical solutions of the thiophene-ethylenedioxythiophene hybrid monomer, the electrochromic material, or the electrochromic glass of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments.

[0109] According to some embodiments of the present invention, the electrochromic product includes at least one of a smart window, a wearable device, and an encrypted information transmission device.

[0110] If there is no special explanation, the protective atmosphere mentioned in the present invention is at least one of nitrogen and argon. The specific choice can be determined according to the experimental conditions and has no obvious effect on the experimental results.

[0111] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0112] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0113] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0114] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0115] Figure 1 It is a spectroelectrochemical diagram of the electrochromic material (P(EDOT-2T)) obtained in the application example of the present invention.

[0116] Figure 2 It is a spectroelectrochemical diagram of the electrochromic material (P(EDOT-3T)) obtained in the application example of the present invention.

[0117] Figure 3 It is the transmittance-time curve of the electrochromic material obtained in the application example of the present invention at 560nm, 767nm and 1100nm.

[0118] Figure 4 It is the transmittance-time curve of the electrochromic material obtained in the application example of the present invention at 567nm, 793nm and 1100nm.

[0119] Figure 5 It is the anodization curve of the thiophene-ethylenedioxythiophene hybrid monomer obtained in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0120] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0121] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0122] Material preparation example

[0123] In this example, 5-tributyltin-3,4-ethylenedioxythiophene was prepared, and the specific steps were as follows:

[0124] A1. Under argon protection, 5 g of EDOT (CAS: 126213-50-1) was dissolved in 100 mL of anhydrous THF (CAS: 109-99-9) to form a THF solution of EDOT;

[0125] The obtained THF solution was cooled to -78°C, and 16.88 mL of a hexane (CAS: 110-54-3) solution (2.5 mol / L) of n-BuLi (CAS: 109-72-8) was added dropwise to the cooled THF solution within 30 min (the addition rate does not affect the performance and yield of 5-tributyltin-3,4-ethylenedioxythiophene, and it can be directly poured in actual production);

[0126] The resulting mixture was kept at -78 °C for 3 h;

[0127] A2. Slowly add 10.73 mL of tributyltin chloride (CAS: 1461-22-9) (dropping speed of about 1 s / drop, each drop is about 0.05 mL) to the mixture obtained in step A1, raise the temperature to room temperature (about 25°C), and continue to stir the resulting mixture at room temperature for 12 h.

[0128] A3. The mixture obtained in step A2 was washed with water (equivalent to two extractions with a total water consumption of 4 L) to remove THF and impurities, and then the water mixed in the organic phase was removed by rotary evaporation under reduced pressure to obtain 5-tributylstannyl 3,4-ethylenedioxythiophene.

[0129] Example 1

[0130] In this example, a thiophene-ethylenedioxythiophene hybrid monomer, specifically EDOT-T, was prepared in the following steps:

[0131] S1. Under the protection of nitrogen, 2,5-bromothiophene (2.1 mmol, 0.5 g, CAS: 3141-27-3), 5-tributylstannyl 3,4-ethylenedioxythiophene (5.25 mmol, 2.26 g, from the material preparation example) and catalyst Pd (PPh 3 ) 4 (0.084mmol, 0.097g, CAS: 14221-01-3) was added to a 250mL single-necked flask. N,N-dimethylformamide (20mL) and dried anhydrous toluene (80mL) were added to the flask and then stirred thoroughly to ensure a uniform mixture. Subsequently, the mixture was heated to 120°C and maintained at this condition for condensation reflux reaction for 48h.

[0132] S2. After the reaction is completed, the resulting mixture is cooled to room temperature (about 25°C), and the cooled mixture is filtered using diatomaceous earth (diatomaceous earth is placed at the bottom of the Buchner funnel, and the mixture is filtered using the Buchner funnel) to remove part of the salt (collect the filtered organic phase); 50 mL of dichloromethane is used to rinse the residual material on the Buchner funnel (collect the rinsed organic phase), and this process is repeated 4 to 5 times to obtain the organic phase. Afterwards, 1500 mL of water is added to the organic phase obtained by filtration and rinsing to wash the organic layer (O / A ratio is 1:5). Next, the mixed solvent in the washed organic phase is removed by reduced pressure distillation and rotary evaporation.

[0133] In order to further purify the product, silica gel column chromatography was used for separation, wherein the eluent ratio was a mixture of dichloromethane and petroleum ether (DCM:PE) in a volume ratio of 1:3, and the resulting solution was eluted and further rotary evaporated to obtain a solid product. After purification, 70 mg of a yellow solid was obtained (yield of about 10%).

[0134] Example 2

[0135] This example prepares a thiophene-ethylenedioxythiophene hybrid monomer, specifically EDOT-2T. The specific steps are different from those in Example 1 in that:

[0136] (1) 2,5-bromothiophene in step S1 was replaced with 5,5'-dibromo-2,2'-bithiophene (0.93 mmol, 0.3 g, CAS: 4805-22-5);

[0137] Correspondingly, in step S1, the amount of 5-tributylstannyl 3,4-ethylenedioxythiophene used is 2.046 mmol;

[0138] Further correspondingly, in step S1, the catalyst Pd(PPh 3 ) 4 The dosage is 0.0372 mmol.

[0139] (2) In step S2, the product is 70 mg of dark orange solid (yield about 16.9%).

[0140] Example 3

[0141] This example prepares a thiophene-ethylenedioxythiophene hybrid monomer, specifically EDOT-3T. The specific steps are different from those in Example 1 in that:

[0142] (1) 2,5-bromothiophene in step S1 was replaced with 5,5"-dibromo-[2,2':5',2"]terthiophene (1.2 mmol, CAS: 98057-08-0);

[0143] Correspondingly, in step S1, the amount of 5-tributylstannyl 3,4-ethylenedioxythiophene used is 3 mmol;

[0144] Further correspondingly, in step S1, the catalyst Pd(PPh 3 ) 4 The dosage is 0.048 mmol.

[0145] (2) In step S2, the product is 180 mg of orange solid (yield about 28.7%).

[0146] Application Examples

[0147] In this example, an electrochromic glass is prepared, and the specific steps are as follows:

[0148] It was carried out using a three-electrode system;

[0149] Electrolyte: 10 mL of DCM was used as the electrolyte, to which 0.01 mol / L of thiophene-ethylenedioxythiophene hybrid monomer (EDOT-T, EDOT-2T or EDOT-3T) from the examples and 0.1 mol / L of tetrabutylammonium phosphorus hexafluoride (Bu 4 NPF 6 , CAS: 3109-63-5, as electrolyte);

[0150] Atmosphere: Protective atmosphere;

[0151] Reference electrode: Ag / AgCl electrode;

[0152] Counter electrode: platinum wire;

[0153] Working electrode: ITO conductive glass;

[0154] Method: Constant potential electrochemical deposition was performed at a voltage of 0.6 V for 40 seconds to obtain electrochromic glass deposited with electrochromic materials (P(EDOT-T), P(EDOT-2T), or P(EDOT-3T)).

[0155] Test Example 1

[0156] In the first aspect of this example, the nuclear magnetic hydrogen spectrum of the thiophene-ethylenedioxythiophene hybrid monomer obtained in the example was tested, and the test results showed that:

[0157] The results of Example 1 are: 1 H NMR (400 MHz, CDCl 3 )δ:7.12(s,2H),6.21(s,2H),4.38-4.33(m,4H),4.27-4.23(m,4H).

[0158] The test results of Example 2 are: 1 H NMR (400 MHz, CDCl 3 )δ:7.11(d,J=3.8Hz,2H),7.07(d,J=3.8Hz,2H),6.23(s,2H),4.38-4.34(m,4H),4.27-4.24(m,4H).

[0159] The test results of Example 3 are: 1 H NMR (400 MHz, CDCl 3 )δ7.19-6.99(m,6H),6.24(s,2H),4.4-4.23(m,8H).

[0160] According to the above results, it can be seen that Examples 1 to 3 of the present invention indeed obtained the products they claimed to obtain.

[0161] In the second aspect of this example, the anodization curve of the thiophene-ethylenedioxythiophene hybrid monomer obtained in the example was tested, and the results showed that the initial oxidation potential of EDOT-T was 0.55V; the initial oxidation potential of EDOT-2T was 0.55V; and the initial oxidation potential of EDOT-3T was 0.6V. The specific test results are as follows Figure 5 shown.

[0162] The third aspect of this example tests the absorption spectrum variation trend of the electrochromic glass obtained in the application example under different voltages. The test voltage is -0.35V to 1.3V, and several point values ​​are selected in between. The absorption spectrum is obtained by using a UV-visible spectrophotometer.

[0163] The test results show that after applying potential, the ultraviolet absorption spectrum peaks of P(EDOT-2T) and P(EDOT-3T) at about 365nm gradually increase and reach the highest absorption peak at about 560nm; the highest absorption peak is attributed to the π-π* transition. In contrast, P(EDOT-T) exhibits similar phenomena at 344nm~403nm. The optical band gaps of P(EDOT-2T) and P(EDOT-3T) are 1.75eV and 1.72eV, respectively. As the oxidation process continues (positive pressure is applied), the intensity of the neutral bands of P(EDOT-2T) and P(EDOT-3T) weakens, and new bands are formed at about 656nm and about 767nm, respectively, indicating the generation of polarons. The specific test results are as follows Figures 1-2 shown.

[0164] Test Example 2

[0165] This example studies the dynamics of the electrochromic material layer on the electrochromic glass obtained in the application example. The specific method is: use a UV-visible spectrophotometer to measure the transmittance of the electrochromic material in the oxidized state (applying positive pressure) and the reduced state (applying negative pressure) under a square wave potential (-0.45~0.8V, interval 5s), so as to calculate the optical contrast (the difference between the upper and lower limits of the transmittance), the impact time, etc. The UV-visible spectrophotometer records the time-transmittance curve, and the electrochemical workstation records the time-current curve. Based on these two curves, the coloring efficiency can also be calculated.

[0166] The test results show that at 1100nm, the optical contrast of P(EDOT-2T) is 44.2%, and the optical contrast of P(EDOT-3T) is 44.3%, and they have excellent stability within 300s. Figures 3-4 As shown in Table 1; in the figure, one cycle represents a period of redox change.

[0167] Table 1 Stability results of electrochromic polymers

[0168]

[0169] In Table 1, examples of the electrical activity retention rates are explained as follows:

[0170] The ratio of the integrated area of ​​the 100th cycle to the integrated area of ​​the 1st cycle.

[0171] Test Example 3

[0172] This example studies the electrochromic performance of the electrochromic material layer on the electrochromic glass obtained in the application example, especially its coloring efficiency.

[0173] Coloring efficiency refers to the ratio of the change in absorbance of an electrochromic material at a given wavelength to the total electron injection or extraction that results.

[0174] For an electrochromic material, coloring efficiency is an important parameter for evaluating material performance. The study of coloring efficiency should be combined with the electrochemical and spectral changes of the electrochromic material film layer. The calculation formula is as follows:

[0175] CE=ΔOD / Q d ;

[0176] Among them, Q d Usually refers to the charge, that is, the amount of charge injected into the electrochromic material; the change in optical contrast (ΔOD) refers to the change in light contrast at a specific wavelength λ max Under the condition of electrochemical oxidation and reduction of electrochromic materials, the corresponding transmittance value (transmittance T of electrochromic materials in doped state (oxidized state)) ox and the transmittance T in the neutral state (not oxidized or reduced) red ) is calculated by the following formula:

[0177] ΔOD=log(T ox / T red );

[0178] Through similar Figure 3 , 4 The coloring efficiency of polymers P(EDOT-T), P(EDOT-2T) and P(EDOT-3T) were calculated based on the middle curve, and the results are shown in Table 2.

[0179] Table 2 Electrochromic parameters of P(EDOT-T), P(EDOT-2T) and P(EDOT-3T)

[0180]

[0181]

[0182] In Table 2, the response time is the time required from the neutral state to the oxidized state / oxidized state to the reduced state, which can be read directly from the graph. ΔT is the change in transmittance (oxidized state and neutral state), which can be read from the graph. Figures 3-4 This can be seen in the kinetic diagram.

[0183] In summary, the thiophene-ethylenedioxythiophene hybrid monomer provided by the present invention has excellent performance, and the electrochromic material film layer formed by in-situ polymerization and deposition on the surface of ITO glass has advantages in thickness, uniform texture, excellent electrochemical stability and coloring efficiency, rapid response and high optical contrast. It is precisely because of the above advantages that the thiophene-ethylenedioxythiophene hybrid monomer provided by the present invention, or the electrochromic material or electrochromic glass prepared therefrom, is expected to be widely used in the preparation of electrochromic products.

[0184] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A thiophene-ethylenedioxythiophene hybrid monomer, characterized in that: The thiophene-ethylenedioxythiophene hybrid monomer is at least one of the compounds represented by Formula I to Formula III:

2. A method for preparing a thiophene-ethylenedioxythiophene hybrid monomer as claimed in claim 1, characterized in that: The preparation method comprises the following steps: A Stille / Suzuki palladium-catalyzed cross-coupling reaction was performed between the halogenated thiophene monomer and 5-tributyltin-3,4-vinyldioxythiophene; The structural formula of the halogenated thiophene monomer is shown in any one of Formula IV to Formula VI: Wherein, R is a halogen atom.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the halogenated thiophene monomer to the 5-tributyltin-3,4-ethylenedioxythiophene is 1:2 to 2.

5.

4. The preparation method according to claim 2 or 3, characterized in that: The temperature of the Stille / Suzuki palladium-catalyzed cross-coupling reaction is 110 to 130° C.; and / or, the duration of the Stille / Suzuki palladium-catalyzed cross-coupling reaction is 24 to 48 hours.

5. An electrochromic material, characterized in that: The electrochromic material is a polymerization product of the thiophene-ethylenedioxythiophene hybrid monomer described in claim 1.

6. A method for synthesizing an electrochromic material as claimed in claim 5, characterized in that: The synthesis method comprises electrochemically polymerizing the thiophene-ethylenedioxythiophene hybrid monomer.

7. An electrochromic glass, characterized in that: The electrochromic glass comprises an ITO substrate layer, and the electrochromic material as claimed in claim 5 attached to the surface of the ITO substrate layer.

8. A method for manufacturing electrochromic glass according to claim 7, characterized in that: The manufacturing method comprises the following steps: in a three-electrode system, using ITO glass as a working electrode, using a liquid phase containing the thiophene-ethylenedioxythiophene hybrid monomer as an electrolyte, and electrochemically depositing the electrochromic material on the working electrode at a constant voltage.

9. The manufacturing method according to claim 8, characterized in that: The voltage of the constant voltage electrochemical deposition is 0.6-0.9V; and / or the duration of the constant voltage electrochemical deposition is 20-50s.

10. An electrochromic product, characterized in that: The raw materials for preparing the electrochromic product include the thiophene-ethylenedioxythiophene hybrid monomer as claimed in claim 1, or the electrochromic material as claimed in claim 5, or the electrochromic glass as claimed in claim 7.

Citation Information

Patent Citations

  • Charge-transporting varnish, charge-transporting thin film, and organic electroluminescent device

    CN104629591A

  • Multi-color changeable thiophthene-EDOTs-based electrochromic polymer material and preparation method

    CN109942797A

  • Preparation method of organic polymer film by using pi-conjugated monomer

    CN110240721A

  • Terthiophene derivative, preparation method and application thereof, electrochromic film and preparation method thereof

    CN116655659A

  • Poly (3, 4-ethylenedioxythiophene) and preparation method and application thereof

    CN117327259A